Do Aesthetic Design Principles Predict Visual Appeal of a Simple Control Panel?. (September 2017) - Kent, Travis M.; Carswell, C. Melody; Lee, Michael; Sublette, M.A.
Numerous studies have investigated the relationship between a product's degree of usability and its degree of beauty. Both directions of causality have been demonstrated leading to "what is beautiful is usable" and "what is usable is beautiful hypothesis. Additionally, aesthetic research has demonstrated several principles that elicit a consistent pattern of responses. The current study aimed to investigate the relationship between aesthetics and usability by means of a functional prime. Forty participants rated sixteen stimuli manipulated on four aesthetic principles; prototypicality, symmetry, composition, and shape. Mixed results indicate that certain aesthetic principles interact with one another in a functional usage.